PHRASEOLOGY IN ENGLISH AND THE USAGE OF TRANSPORT PHRASES - Dekhqonboyeva , Madina Ablayor kizi; Akhunov, Mukimjon (Educational Research in Universal Sciences, 2023)
Phraseology is an integral and organic part of both the language system and culture. It is also called a phraseological turnover, a speech turnover - this is a stable combination of words characteristic only of a given language, the meaning of which is not determined by the meaning of the words included in it, taken separately. That is, words that are part of phraseological units more or less lose their own lexical meaning. Thus, the phraseological unit is used as a whole, ready-made phrase. The combination of the meanings of the words included in it is the lexical meaning of the entire phraseological unit. The following article is devoted to phraseology related to transportation in the English language.